Gotham. The complete second season - Cannon, Danny; Bailey, Rob (Robert); McKenzie, Ben, 1979-; Logue, Donal, 1966-; Mazouz, David, 2001- (Burbank, CA : Warner Bros. Entertainment, 2016)
Follows James Gordon during his early days of the Gotham City Police Department.
Damned if you do... -- Knock knock -- The last laugh -- Strike force -- Scarification -- By fire -- Mommy's little monster -- Tonight's the night -- A bitter pill to swallow -- The son of Gotham -- Worse than a crime -- Mr. Freeze -- A dead man feels no cold -- This ball of mud and meanness -- Mad grey dawn -- Prisoners -- Into the woods -- Pinewood -- Azrael -- Unleashed -- A legion of horribles -- Transference.
Anamorphic wide screen 1.78:1.
Features: Gotham : 2015 Comic-Con panel, Gotham by noir light, Alfred : Batman's greatest ally, Cold hearted : the tale of Victor Fries, FOX network featurettes pieces.
Ben McKenzie, Donal Logue, David Mazouz, Sean Pertwee, Robin Lord Taylor.
Originally broadcast on television 2015-2016.
TV rating: Not rated.
In English with optional English, French, or Spanish subtitles.
Keywords: Police -- Drama; Crime -- Drama; Thrillers (Television programs); Television series; Fiction television programs; Crime television programs